The morphofunctional changes in the skin after long influence of low-scale ionizing radiation - Ja. V. Porovsky; F. F. Tetenev (Бюллетень сибирской медицины, 2002)
We researched musculocutaneous samples in two experimental groups, including 19 Chernobyl liquidation participants and 27 residents of the Siberian chemical combine zone, to trace the changes, which had happened in their skin after a long period of constant small-scale ionizing radiation influence. The analysis showed that the greatest changes had taken place in the epidermis of both groups in the form of thickening of horny and cellular layers and inflammatory infiltration of lymphocytes provided with the productive panvasculitis in the majority of arterioles. It is supposed, that after the long small-scale irradiation influence, in the skin develops two forms of reaction: defense reaction in the form of proliferative hyperkeratosis and immunopathological reaction, which is a consequence of activation in the cellular layer of epidermis combined with the appearance of effector section of immune answer, which stimulates the interaction of epidermal T-lymphocytes with the endothelial cells of derma vessels and participation of blood vessels of microcircular channel.